2022
DOI: 10.1038/s41598-021-04681-y
|View full text |Cite|
|
Sign up to set email alerts
|

Facial mask personalization encourages facial mask wearing in times of COVID-19

Abstract: One of the most cost-effective strategies for fighting the spread of COVID-19 is the use of facial masks. Despite health officials’ strong efforts to communicate the importance or wearing a mask, compliance has been low in many countries. In the present paper we propose a novel behavior-intervention strategy to encourage people to wear facial masks. Three studies show that the personalization of a mask, as a form of identity expression, increases mask wearing intentions and, by extension, the percentage of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Regarding the aspects of personalized health wellness based on novel materials for diagnostic, treatment, and antibacterial performance [ 18 , [36] , [37] , [38] , [39] ], everyone should pay special attention to indoor air quality as we do for water and food quality. The health consequences in case of contaminated air are noticeably serious and now are well-explored.…”
Section: Conclusion and Viewpointmentioning
confidence: 99%
“…Regarding the aspects of personalized health wellness based on novel materials for diagnostic, treatment, and antibacterial performance [ 18 , [36] , [37] , [38] , [39] ], everyone should pay special attention to indoor air quality as we do for water and food quality. The health consequences in case of contaminated air are noticeably serious and now are well-explored.…”
Section: Conclusion and Viewpointmentioning
confidence: 99%
“…In conclusion, the estimated results suggest that although the mask requirement does not amplify the vaccine effect for all areas, it greatly amplifies the vaccine effect in reducing the viral burden against the disease infection for areas with core airport hubs, high population density, and vulnerable people even with the presence of the Delta variant. Palcu et al (2022) 14 also suggested that facial masks should be encouraged even after the vaccine is available.…”
Section: Figurementioning
confidence: 99%
“…Indeed, the larger airport hubs 9 is an important indicator that produces a high influx of imported infections and boosts the local transmission of the virus. Besides, the local disease dynamics is greatly influenced by factors such as the demographic characteristics 10,11 , the presence of disease variants 4,5 , the protective behavior from imposed policies (e.g., mask requirement) [12][13][14] , mobility index and social contacts 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…A total of 39 out of 50 states in the United States implemented statewide mask-wearing mandates as a means of limiting the transmission of the novel coronavirus. Although mask mandates may have provided some with a reduction in anxiety because of added protection from the coronavirus or mitigating sources of social anxiety [17], wearing a face mask may be perceived as restrictive or uncomfortable [18] as well as something that may threaten personal freedom [19]; therefore, it is reasonable to believe that mental reactions to the requirement of masking were heterogeneous and often adverse both across the country and throughout this phase of the pandemic. Reasons for an adverse response are manifold and need not be restricted to groups rather than to masking.…”
Section: Introductionmentioning
confidence: 99%